2015
DOI: 10.1016/j.ntt.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral impairments caused by developmental imidacloprid exposure in zebrafish

Abstract: BACKGROUND Neonicotinoid insecticides are becoming more widely applied as organophosphate (OP) insecticides are decreasing in use. Because of their relative specificity to insect nicotinic receptors, they are thought to have reduced risk of neurotoxicity in vertebrates. However, there is scant published literature concerning the neurobehavioral effects of developmental exposure of vertebrates to neonicotinoids. METHODS Using zebrafish, we investigated the neurobehavioral effects of developmental exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 37 publications
9
63
2
1
Order By: Relevance
“…We show that exposure of zebrafish larvae to A6 induces larval mortality at the relatively low concentration of 0.5 μM, with marked effects on the nervous system, both central and sensory. Similar lethalities have been reported for other pesticides tested on zebrafish larvae [35,36,37]. Using the well-defined and easily accessible lateral line sensory system as an assay, we observed that A6 affects axonal regeneration at the low dose of 50 nM, suggesting that this compound may have serious long-term effects on neural plasticity and repair at these low doses.…”
Section: Discussionsupporting
confidence: 84%
“…We show that exposure of zebrafish larvae to A6 induces larval mortality at the relatively low concentration of 0.5 μM, with marked effects on the nervous system, both central and sensory. Similar lethalities have been reported for other pesticides tested on zebrafish larvae [35,36,37]. Using the well-defined and easily accessible lateral line sensory system as an assay, we observed that A6 affects axonal regeneration at the low dose of 50 nM, suggesting that this compound may have serious long-term effects on neural plasticity and repair at these low doses.…”
Section: Discussionsupporting
confidence: 84%
“…There is also the possibility that the neonicotinoids have affected the anxiety of the wood frogs because nAChRs, where neonicotinoids bind in the nervous system, are involved in anxiety-like behaviors in mice (Drago et al 2003). Crosby et al (2015) conducted the first targeted assessment of the behavioral effects of imidacloprid on an aquatic vertebrate, using a fish model species, the zebrafish (Danio rerio). They assessed the developmental neurotoxicity of larval aquatic exposure to imidacloprid (and nicotine) on zebrafish as larvae immediately after exposure and during adolescence and adulthood after exposure had ceased for 1.5 and 3 mo, respectively (Crosby et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we (Crosby and others 2015) investigated in zebrafish the neurobehavioral effects of developmental exposure to imidacloprid, a prototypic neonicotinoid pesticide. Nicotine was also administered for comparison.…”
Section: Neonicotinoids (Nes)mentioning
confidence: 99%